Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1021/acsomega.8b02672
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights into Destabilization of Alzheimer’s Aβ Protofibril by Arginine Containing Short Peptides: A Molecular Modeling Approach

Abstract: Aggregation of amyloid beta (Aβ) peptides leads to formation of fibrilar, soluble oligomers, and their deposition is a key event in progression of Alzheimer’s disease (AD). Recent experimental studies of Arg-Arg-7-amino-4-trifluoromethylcoumarin (RR-AFC) showed significant Aβ aggregation inhibition, but its molecular mechanism is not yet clear. Hence, the present study aims at exploring the underlying mechanism of destabilization and inhibition of aggregation of the Aβ protofibril by RR-AFC at the molecular le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“…Homology modelling and molecular docking techniques have been found useful to investigate folding pattern and molecular interactions between several enzymes and ligands [33][34][35][36][37][38][39][40][41][42] Binding affinities of Camostat mesylate, Nafamostat and Bromhexine hydrochloride to the active site of modelled protein, TMPRSS2 were confirmed by Autodock 4.2 computational tool with Lamarckian Genetic Algorithm (LGA) [43]. Here, also blind docking was performed by taking protease domain in grid box.…”
Section: Molecular Docking By Autodockmentioning
confidence: 99%
“…Homology modelling and molecular docking techniques have been found useful to investigate folding pattern and molecular interactions between several enzymes and ligands [33][34][35][36][37][38][39][40][41][42] Binding affinities of Camostat mesylate, Nafamostat and Bromhexine hydrochloride to the active site of modelled protein, TMPRSS2 were confirmed by Autodock 4.2 computational tool with Lamarckian Genetic Algorithm (LGA) [43]. Here, also blind docking was performed by taking protease domain in grid box.…”
Section: Molecular Docking By Autodockmentioning
confidence: 99%
“…The major factors that were considered by most of the researchers for evaluating the destabilization potential of the ligands are secondary structure content especially beta and coil content, salt bridge distance between Asp23-Lys28 (especially in U-shaped model), inter-chain hydrogen and hydrophobic interaction. 64,65,[81][82][83][84][85][86][87] In the current work, it was observed that binding of peptides with Abeta protobril has resulted in the loss of beta structure and gain of coil structure. This is in accordance with previous studies showing increase of coil and decrease of beta structures.…”
Section: Discussionmentioning
confidence: 86%
“…They also showed that it destabilize the protobril by disrupting the native inter-chain D23-K28 salt bridges, decreasing inter-chain backbone hydrogen bonds and rearranges the tightly compact b-strand-bend-b-strand motifs by increasing the interchain A21-V36 distance. In another study, Barale et al 87 showed that binding of arginine hybrid peptides to Abeta protobril destabilize it by breaking of important salt bridge between D23-K28. Gupta et al 65 showed the destabilization ellagic acid (REF) using molecular dynamic simulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Homology modelling and molecular docking techniques have been found useful to investigate folding pattern and molecular interactions between several enzymes and ligands [33][34][35][36][37][38][39][40][41][42] AutoDock and UCSF chimera [31].…”
Section: Molecular Docking By Autodockmentioning
confidence: 99%